How does Internet access quality affect learning outcomes? : A multiple mediation analysis among international students in China - Ren, Wei; Zhu, Xiaowen; Liang, Zai (Journal of International Students, 2024)
The study explored how the quality of Internet access influenced students’ online learning experiences during the pandemic-imposed large-scale adoption of online education. Drawing upon digital inequality research, we analyzed data collected from 894 higher education international students in China. We found that both access devices and Internet stability exerted significant impacts on international students’ satisfaction with and performance of synchronous online learning (SOL). The path model further revealed that the underlying mechanisms through which the two dimensions of access inequality affected learning outcomes were different. While the effects of access devices on learning satisfaction and course performance were only mediated by adaptability to online pedagogy, Internet stability affected the two outcome variables via both interaction and adaptability. The study highlights the implications of these findings in the context of online education.